PREMARITAL SEXUAL BEHAVIOR AMONG ADOLESCENTS IN KOTO RAJO, KUANTAN HILIR SEBERANG DISTRICT ,KUANTAN SINGINGI REGENCY - Jas Adi Putra; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This research was conducted in Koto Rajo village, Kuantan Hilir Seberang District, Kuantan Singingi Regency. The sampling method of this research was the guided interview method which doing the direct observation. The data analysis method was done by the existing data was classified according to the main problem of this research. This data would be analyzed by descriptive qualitative by giving an overview of how the real condition was. The result of this research showed us that mostly of the respondents were 20 years old, Malay and Tigo Kampuong tribe.There were several factors that influenced the premarital sexual behavior, the first factor was sexual libido; a desire in doing sexual activity. For the women, sexual desire could be interpreted as an impulse of someone’s desire overall. The second factor was the maturity of marriage age, it was the efforts to increase the age of the first marriage, and therefore it could reach the minimal age; 20 years old for the women and 25 years old for the men. Besides, taboo was a social prohibition of the words, things, activities, and unwanted person in the tribe, culture, and society. The violation of the taboo usually unacceptable even interpreted as an attack. In addition, free social intercourse was one of the diverge behavior, where “free” meant beyond the boundaries of the oriental norm itself. We often heard the problem of this free social intercourse in the environment even in mass media.Keywords: Sexual behavior, Adolescents, Characteristics, premarital sex